2006
DOI: 10.1002/jms.1104
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of ion formation from the aqueous solutions irradiated with 3 µm IR laser pulses under atmospheric pressure

Abstract: The mechanism of atmospheric pressure (AP) laser ionization of water and water/glycerol liquid samples at a 3-microm wavelength is studied experimentally. For the ion desorption, an in-house built Yb : YAG-pumped optical parametric oscillator (OPO) infrared (IR) laser has been coupled with AP MALDI ion source interfaced to an ion trap mass spectrometer (MS). It has been shown that water is primarily responsible for ion generation in water/glycerol samples, while glycerol increases the solution viscosity and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 8 publications
0
14
1
Order By: Relevance
“…This mechanism is likely to be more pronounced in IR-MALDI where a greater extent of cluster/droplet desorption occurs compared to UV-MALDI [29,30]. Enhancement of analyte ion signal has been observed in the presence of corona ions for AP-IR-MALDI and the effect has been attributed to neutral ionization [5,6,31]. However, no direct experimental evidence has been presented for this mechanism.…”
Section: Further Mechanistic Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism is likely to be more pronounced in IR-MALDI where a greater extent of cluster/droplet desorption occurs compared to UV-MALDI [29,30]. Enhancement of analyte ion signal has been observed in the presence of corona ions for AP-IR-MALDI and the effect has been attributed to neutral ionization [5,6,31]. However, no direct experimental evidence has been presented for this mechanism.…”
Section: Further Mechanistic Considerationsmentioning
confidence: 99%
“…However, no direct experimental evidence has been presented for this mechanism. In addition, it has recently been suggested that large charged molecular clusters and/or small droplets desorbed in AP-IR-MALDI could be major contributors to the ion generation process via disintegration in the heated capillary of the MS inlet [31]. Accordingly, further charging of the clusters/droplets by corona ions could be a plausible mechanism for the observed signal enhancement in AP-IR-MALDI.…”
Section: Further Mechanistic Considerationsmentioning
confidence: 99%
“…Therefore, the decrease in the diffusion of particles would not have had a significant influence on the increase in the ion signal intensity. Laiko et al have reported that the dependence of the ion signal intensity on the voltage between the sample plate and the inlet to the mass spectrometer in AP‐IR‐MALDI is quite different from that in AP‐UV‐MALDI and that ions can be observed even when the voltage is not applied between the sample plate and the inlet to the mass spectrometer . They concluded that the charged and uncharged microdroplets produced by IR laser irradiation move mostly under the influence of gas flow of the differential pumping.…”
Section: Resultsmentioning
confidence: 99%
“…Under these conditions, the ablated material is mainly from the surface of the droplet rather than the bulk, leading to direct droplet surface analyses. Material ablation by 2.94-μm IR laser occurs via phase explosion at the droplet surface, releasing microdroplets containing analytes 13,15. These microdroplets can produce gaseous ions for mass spectrometry either by direct charging of the parent droplet or via coalescence with the ESI plume.…”
Section: Resultsmentioning
confidence: 99%